Metal‐Free Oxidative para Cross‐Coupling of Phenols. Issue 27 (21st May 2013) - Morimoto, Koji; Sakamoto, Kazuma; Ohnishi, Yusuke; Miyamoto, Takeshi; Ito, Motoki; Dohi, Toshifumi; Kita, Yasuyuki
<x xml:space="preserve">Abstract</x> CC coupling: Direct oxidative coupling reactions are an attractive tool for environmentally benign chemistry. The oxidative biaryl coupling reaction of phenols with various arenes at the para positions with hypervalent iodine reagents may also be included in this category. The reaction proceeds under very mild conditions without metal catalysts in a very short time under ambient conditions (see scheme; HFIP=hexafluoroisopropanol).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>